Perubahan Karakteristik Fisik Belimbing Wuluh selama Fermentasi Asam Sunti - Murna Muzaifa (Agricultural Faculty, 2013)
Asam sunti is a product of bilimbi (Averrhoa bilimbi L.) fermentation, traditional ingredient from Nanggroe Aceh Darussalam, used as flavor, particularly to provide sour taste and specific aroma in Acehnese cuisine. Scientific studies of asam sunti are relatively limited, while study of change on physical and chemical characteristics of asam sunti does not exist. The objective of this research was to study the change of physical characteristics of bilimbi during fermentation. This study used explorative laboratory design. Asam sunti was produced in laboratory scale with three times repetition and sample was taken three times in stages, i.e., before sun-drying and salting (stage 1), after repeated sun-drying and salting (stage 2), and fermentation for 1 month (stage 3). Parameters analyzed on physic characteristics included aw, texture and color. Significant change on physic characteristics were found during the processing of bilimbi to become asam sunti. The value of aw of the bilimbi was found to decrease after processing (sun-drying and salting) and fermentation for 1 month. Texture of the bilimbi increased at stage 2 and decreased at the last of fermentation. The colour of the bilimbi changed from green to brown after the whole processing (salting, drying and fermentation).